Psychometric Properties of the Persian Version of Informant Questionnaire on Cognitive Decline in the Elderly-Short Form (IQCODE-S): Informant Questionnaire on Cognitive Decline in the Elderly-Short Form (IQCODE-S) - Azarnivand 1, Maryam; Dadgari 2*, Ali; Goli 3, Shahrbanoo; Foroughan 4, Mahshid (Shahroud Journal of Medical Sciences, 2019)
Background: Dementia and cognitive decline mainly affect older people. Several instruments have been developed for screening and detection of cognitive impairments, among them is the short form of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE-S).; however, there was no instrument to assess it in Persian language speakers. The purpose of the present study was to validate the Persian version of the Informant Questionnaire on Cognitive Decline in the Elderly-Short Form (IQCODE-S). Methods: In this study, WHO's standard 'forward-backward' translation procedure was performed. The validity and reliability of the questionnaire were evaluated and it was administered in a sample of 373 inpatient Iranian elderlies. The convenient sampling was performed to include participants from family members caregiving older patients with long diagnosed of dementia. Face and content validity were evaluated and the reliability of the instrument was evaluated. Results: The mean age of the participants was 71.08 ± 9.89 years. Cronbach’s alpha coefficient was .82. Significant correlations were observed between cognitive status and age, marital status, education and hospitalized wards (p < .05). Appropriate CVI and were calculated as .85 and.7 respectively. Conclusion: This study reports on translation and validation of the Persian version of one of the most important screening tools for dementia. It reveals a significant association between the elderlies’ cognitive decline and their age, marital status, education, and hospitalized ward. Key words: Psychometrics, Ageing, Cognitive Decline, Informant